2018
DOI: 10.1002/naaq.10011
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Emulsifiers to Hydrogenated Soybean Oil‐Based Feeds for Yellowtail

Abstract: Hydrogenated soybean oil can be used to spare fish oil in aquafeeds, but lipid digestibility may be a limiting factor. We evaluated the performance and tissue fatty acid composition of juvenile Yellowtail Seriola dorsalis that were fed diets containing menhaden fish oil (positive control), hydrogenated soybean oil (negative control), or hydrogenated soybean oil amended with 1% mixed bile acids, casein, whey protein, or monoglycerides as emulsifying agents. Juvenile fish (~10 g) were stocked in a semi-closed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Digestibility and utilization of these and other SFA‐rich lipids constitute an area of ongoing concern (Bergman et al. ); the effects of SFA‐rich lipids on tissue lipid content will also have to be considered when using LC‐PUFA sparing to enhance or maintain fillet nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…Digestibility and utilization of these and other SFA‐rich lipids constitute an area of ongoing concern (Bergman et al. ); the effects of SFA‐rich lipids on tissue lipid content will also have to be considered when using LC‐PUFA sparing to enhance or maintain fillet nutritional value.…”
Section: Discussionmentioning
confidence: 99%
“…Emulsifier-like feed additives have been widely used in terrestrial animals [1][2][3][4][5][6]. In recent years, they are also being more and more frequently used in farmed fish, typically bile acids [7,8]. The positive effects of bile acids on growth and lipid metabolism of farmed fish have been reported in a number of studies [9][10][11][12][13][14][15][16][17], including a recent study of ours with a marine teleost, tiger puffer (Takifugu rubripes) [18].…”
Section: Introductionmentioning
confidence: 97%
“…The effects of supplemental emulsifiers including lecithin, lysolecithin, bile acids and phosphatidylcholine (PC), on the growth rates, feed digestion and absorption have been tried in marine fishes (Benedito‐Palos et al, 2008; Bergman et al, 2018; Feng et al, 2017; Fountoulaki et al, 2009; Liu et al, 2002), freshwater fishes (Azarm et al, 2012; Sink & Lochmann, 2014); and shrimp (Khan et al, 2018). Results indicated that these emulsifiers can improve fish performance, feed efficiency, survival and immune response.…”
Section: Introductionmentioning
confidence: 99%